Estrutura da ictiofauna e ecologia trófica de Sciaenidae acompanhante na pesca do camarão sete-barbas, no litoral de Santa Catarina, Brasil - Sabinson, Lia Mayrink (2014)
In trawling a significant portion of the captured fauna has no commercial value and is returned to the sea, causing biological and ecological changes, with impacts on the food chain, modifying processes of energy transfer in the ecosystem. Studies on the feeding habits of demersal fish provide basic information for understanding species trophic relations. Thus, this work aimed the undestandment of the feeding habits of the most abundant fish present in the bycatch of the Xiphopenaeus kroyeri artisanal fisheries of the coast of Santa Catarina, through the analysis of stomach contents, describing patterns of similarity, overlap and trophic structure. Sampling took place seasonally, from November 2009 to August 2010, in Balneario Barra do Sul, Porto Belo and Penha. Whaling vessels from the artisanal shrimping fleet were used for trawling. After sorting the specimens, they were frozen until the completion of biometrics and stomach content analysis. Information obtained through analysis of stomach contents were quantified via the Kawakami-Vazzoler feeding index, combining the frequency of occurrence and the relative volume of the items. Species of Sciaenidae family were the most abundant. Ctenosciaena gracilicirrhus, Cynoscion jamaicensis, Larimus breviceps, Menticirrhus americanus, Stellifer brasiliensis and S. rastrifer were classified as crab eaters, while Isopisthus parvipinnis crab eater/piscivore, Micropogonias furnieri as annelid eater/crab eater and Paralonchurus brasiliensis as annelid eater, however species were found to have very similar diets, altering the intake of certain items between seasons and locations. According Morisita overlap index, 9 cases of overlap were observed in Balneario Barra do Sul, 9 in Penha and 20 in Porto Belo. The bipartite foodwebs showed generality in the intake of food, with most species carrying multiple trophic interactions. Once the Sciaenidade family is the most abundant and diverse in the sea-bob-shrimp bycatch, iv its removal seems to directly influence the ecosystem processes in the region, with most species performing a wide range of interactions. Therefore their removal will gradually change the stability of benthic community.